Not all convergence is equal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
There is talk of 'convergence' in ICTs, with benefits from links between telephone and computers. The benefits depend on your 'band width' meaning the carrying capacity of the line to your phone. A narrow line (meaning older, cheaper) can handle a...